2012
DOI: 10.1016/j.palaeo.2012.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Organic geochemistry, stable isotopes, and facies analysis of the Early Aptian OAE—New records from Spain (Western Tethys)

Abstract: The Early Aptian Oceanic Anoxic Event (OAEla) is a time interval characterized by increased organic carbon accumulation in marine sediments, notable sedimentary and biotic changes, and abrupt carbon-isotope excursions indicative of significant major palaeoenvironmental changes linked to a perturbation in the global carbon cycle. Here we present the study of four sections recording the OAEl a (Early Aptian) in Spain, which are located in two broad basins respectively located in the South and the North of Iberia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 94 publications
0
14
0
Order By: Relevance
“…120 Ma), organic-rich black shales were deposited in all major ocean basins (e.g. Sliter, 1989;Bralower et al, 1994;Erba et al, 1999;Ando et al, 2002;Takashima et al, 2004;Dumitrescu and Brassell, 2005;Quijano et al, 2012). Although we had rather coarse sample resolution, the compound specific d 13 C values also do not depict the large negative d 13 C shift that is characteristic of OAE 1a (Menegatti et al, 1998;Erba et al, 1999) and recorded as a ca.…”
Section: Depositional Environment In the Angola Basinmentioning
confidence: 91%
“…120 Ma), organic-rich black shales were deposited in all major ocean basins (e.g. Sliter, 1989;Bralower et al, 1994;Erba et al, 1999;Ando et al, 2002;Takashima et al, 2004;Dumitrescu and Brassell, 2005;Quijano et al, 2012). Although we had rather coarse sample resolution, the compound specific d 13 C values also do not depict the large negative d 13 C shift that is characteristic of OAE 1a (Menegatti et al, 1998;Erba et al, 1999) and recorded as a ca.…”
Section: Depositional Environment In the Angola Basinmentioning
confidence: 91%
“…However it has been argued that in overmature OM the original n-alkane composition can be altered leading to conflictive results (Quijano et al, 2012). Since Bernaus et al (2003) reported thermally mature OM for samples studied to the east of the El Pui section in the Organyà Basin;…”
Section: Biomarker Analysismentioning
confidence: 99%
“…This means that fluctuations in the percentage of abundances of this taxon probably do not represent a direct response to environmental changes, but may reflect a measure of the success of other species (Aguado et al, 2014) High abundances of Micrantholithus are recorded at the base of the section. This group was considered as a marginal or neritic taxon and its abundance has been related to neritic factors such as reduced salinity (Roth and Bowdler, 1981;Street and Bown, 2000;Bersezio et al, 2002;Bown, 2005;Tremolada et al, 2009;Quijano et al, 2012).…”
Section: Calcareous Nannofossils As Palaeoenvironmental Indicatorsmentioning
confidence: 99%